Phase II trial of a novel chemotherapy regimen CVEP (cyclophosphamide, vinblastine, etoposide and prednisolone) for acquired immunodeficiency syndrome (AIDS)‐associated lymphomas. (2nd November 2022) - Sengar, Manju; Jain, Hasmukh; Shet, Tanuja; Sridhar, Epari; Gota, Vikram; Rangarajan, Venkatesh; Laskar, Siddhartha S.; Alahari, Aruna; Thorat, Jayashree; Agarwal, Archi; Sharma, Neha; Gupta, Himanshi; et al.
Summary: Management of acquired immunodeficiency syndrome (AIDS)‐related diffuse large B‐cell (DLBCL) and plasmablastic lymphomas (PBL) poses significant challenges. The evidence supports use of dose‐adjusted EPOCH (etoposide, prednisone, vincristine, cyclophosphamide and doxorubicin) with or without rituximab as first‐line therapy. The need for central venous access, growth factors and significant toxicities limits its use in resource‐constrained settings. To address these challenges, we have developed a novel regimen, CVEP (cyclophosphamide, vinblastine, etoposide, and prednisolone) based on the pharmacodynamic principles of dose‐adjusted EPOCH. This single‐centre phase II study evaluated the efficacy and safety of CVEP regimen in patients with de novo systemic AIDS‐related DLBCL and PBL. The primary objective was complete response (CR) rates as assessed by positron emission tomography‐computed tomography. The secondary objectives were incidence of Grade 3/4 toxicities, toxicities requiring hospitalisation, and disease‐free survival. From May 2011 to February 2017, 42 patients were enrolled. At the end of therapy the CR rates were 69% (29/42) in the intention‐to‐treat population and 80.5% (29/36) in evaluable patients. At a median follow‐up of 69 months, the 5‐year disease‐free survival was 65.3%. Out of 217 cycles administered, febrile neutropenia occurred in 19.3% and hospitalisation was required in 18.3% of cycles. There were two treatment‐related deaths. The CVEP regimen is an active and safe regimen for AIDS‐related DLBCL and PBL.